Max Weber, vocation and modernization: Some remarks concerning the disenchantment of the disenchanter - Μόττα, Ρομπέρτο (The Greek Review of Social Research, 2010)
In order to understand the significance of weberianism and its spread, two aspects should be taken into account. On the one hand, the meaning of some concepts. What, for instance, do Beruf mean in Weber’s writings and how does it differ from similar concepts in other systems of thought? Critics have demonstrated beyond a reasonable doubt that the Berufsethik attributed by Weber to Luther and Calvin is in essence the same as the éthique du devoir which was common place among Catholic authors in 17th and 18th centuries. On the other hand, there is the issue of the «use value» of weberianism in countries like Brazil or France. For even if Weber is wrong in his theological treatment of vocation, he remains the outstanding analyzer of the process of rationalization and the announcer, the «philosopher» and indeed the «prophet» of a modernity that he and many of his interpreters have conditioned to the acceptance of the «Protestant Ethic».